Meningkatkan kesadaran finansial generasi muda melalui pelatihan literasi keuangan di sekolah menengah atas - Gosal, Joe Valentino; Wijaya, Joshua; Yosia, Clarence; Linawati, Nanik (Nur Science Institute, 2025)
This community service initiative aimed to enhance financial awareness among high school students at SMAK Petra 2 Surabaya by implementing comprehensive and interactive financial literacy training. The program utilized a service-learning approach integrating active academic learning with community engagement. The activities included interactive lectures, group discussions, a personal financial goal-setting workshop, a digital quiz competition, basic investment education, and an educational card game titled “Stock Quartet.” These components introduced key financial concepts such as budgeting, saving, and investing in an accessible and engaging way. The digital quiz measured students’ comprehension, while the game reinforced stock market understanding in a fun context. Data were collected using the STARS method, direct observation, quiz scores, and analysis of student financial plans. The results showed increased financial literacy, improved savings behavior, and greater student awareness of the importance of early financial planning. This approach effectively cultivated a healthy financial mindset, empowered students to make informed financial decisions, and encouraged long-term financial responsibility. The outcomes indicate that practical and enjoyable financial education can be critical in developing financially literate youth prepared to face future economic challenges.